2014
DOI: 10.1007/s10826-014-0081-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal HIV Illness and its Impact on Children’s Well-being and Development in Haiti

Abstract: Little is known about the impact of parental HIV illness on children’s well-being and development in the island nations of the Caribbean. Study objectives were to examine mothers’ experiences of impact of HIV illness on their children’s well-being and development in Haiti. Baseline interviews were conducted between 2006 and 2007 with 25 HIV-positive mothers as part of a larger study that examined the feasibility of a psychosocial support group intervention for HIV-affected youth and their caregivers in central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(72 citation statements)
references
References 39 publications
0
72
0
Order By: Relevance
“…A similar finding was described in a study among Ugandan HIV‐infected caregivers and children drawn from a separate cohort of the parent trial (Murray et al., ) and is consistent with other qualitative studies among caregivers living with HIV. For example, a study in Haiti described how mothers living with HIV found it challenging to earn sufficient income to provide food and housing for their children and to send their children to school (Conserve et al., ). Regarding caregivers’ comments on keeping their children in good health, findings from this qualitative study should be interpreted within the context of the parent trial, through which caregivers had received a year‐long health and nutrition intervention.…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was described in a study among Ugandan HIV‐infected caregivers and children drawn from a separate cohort of the parent trial (Murray et al., ) and is consistent with other qualitative studies among caregivers living with HIV. For example, a study in Haiti described how mothers living with HIV found it challenging to earn sufficient income to provide food and housing for their children and to send their children to school (Conserve et al., ). Regarding caregivers’ comments on keeping their children in good health, findings from this qualitative study should be interpreted within the context of the parent trial, through which caregivers had received a year‐long health and nutrition intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The general characteristics of the included studies are presented in Table 1. Ten studies (11 articles) were conducted in Asia and the Pacific region, six in Africa (4,6,23,(33)(34)(35), one study (two articles) in Caribbean (11,12), and one study in both Zimbabwe and USA (36). Of the 20 articles, eleven employed face to face qualitative interviews (4,11,12,14,23,24,34,(37)(38)(39)(40).…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…Ten studies (11 articles) were conducted in Asia and the Pacific region, six in Africa (4,6,23,(33)(34)(35), one study (two articles) in Caribbean (11,12), and one study in both Zimbabwe and USA (36). Of the 20 articles, eleven employed face to face qualitative interviews (4,11,12,14,23,24,34,(37)(38)(39)(40). Nine articles used quantitative methods (3,5,6,13,25,33,35,36,41), of which seven were cross-sectional (3,5,6,25,33,35,36) and two were prospective cohort studies (13,41).…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations